Heart rate variability and anthropometric indices in university males of Santiago de Chile - Urbano-Cerda, Sebastián; Fuentes-Barría, Héctor; Vera-Aguirre, Valentina; González-Wong, Catalina; Aguilera-Eguía, Raúl (Universidad y Salud, 2021)
Introduction: Low heart rate variability (HRV) has been associated with autonomic imbalances and cardiovascular risk in various populations. Objective: To relate HRV and anthropometric indices in young, physically active university male students with low cardiometabolic risk. Materials and methods: A descriptive cross-sectional study, which included 10 men aged 23.15 ± 2.91 years, with a Body Mass Index (BMI) of 25.48 ± 2.19 kg / m2, and a Waist-Hip Ratio (WHR) of 0.81 ± 0.02. Resting heart rate variability was measured over a 5 minute period. A correlational analysis was performed between BMI and WHR with the low frequency / high frequency ratio (LF / HF), standard deviation of the instantaneous variation of RR intervals (SD1), and complexity of the RR intervals (α-1). In addition, statistical power (1- β) and effect size (Cohen's "d") were determined. Results: LF / HF is only significantly related to WHR (r = 0.638; p = 0.047; d = 0.80), while SD1 and α-1 did not show any association with BMI and WHR. Conclusions: There is a parasympathetic predominance that suggests a protective mechanism on intra-abdominal adipose tissue related to WHR. Further studies are required to explain all the modulating variables of the heart rate variability.